Adjudicating “broken windows”: a qualitative inquiry of misdemeanor case processing in the New York city’s lower criminal courts - Barrett, Carla J. (Criminology, criminal justice, law & society, 2017)
Extensive scholarly attention has been given to the felony courts while misdemeanor courts have not been as well studied. Due to increased misdemeanor caseloads in the era of order-maintenance policing, the importance of investigating the misdemeanor court landscape cannot be overstated, especially since these lower courts are the courts with which most people have contact. Using open-ended interviews with court actors (prosecutors, defense attorneys, judges, and/or court administrators) inNew York City, this paper examines how the court actors interviewed describe common practices in the day-to-day processing of misdemeanors. These narratives reveal shared concerns over the “worth” of many misdemeanor charges and the direct and collateral consequences of misdemeanor prosecution. These narratives also illustrate how these factors inform the ways by which court actors navigate the terrain of misdemeanor case processing and how they articulate “things that matter” in the face of massive caseloads, providing useful insights into the adjudication of mass misdemeanors.